The Effect Of Investment and employment on Economic Growth : Pengaruh Investasi Dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi - Syaqinah Ujung; Mentari Rezeki Ramadhani; Zulfa Afifah (Outline Journal of Economic Studies, 2023)
This study aims to determine the effect of investment and labor on economic growth. This study uses a qualitative method. In this study, researchers used a data collection method, namely library research or literature by citing several literature studies such as several articles related to problems related to economic growth. The research is descriptive in nature which tends to use analysis that focuses on in-depth observations. Based on the results discussion, the rate of economic growth and investment has a positive reciprocal relationship. This reciprocal relationship occurs because on the one hand, the higher the economic growth of a country, it means that the greater share of income that can be saved, so that the investment created will be even greater. The number of workers in Indonesia has influential results and also chooses a positive relationship with Indonesia's economic growth, with an increase in the number of people working in Indonesia it is hoped that the productivity of the workforce will increase so that this can spur economic growth in Indonesia.